PERGESERAN MEKANISME PEMILIHAN KEPALA DAERAH DI INDONESIA DALAM PERSPEKTIF KONSTITUSIONAL DAN DEMOKRASI - Lukman Ansar; Tarmizi Tarmizi; Lisma Lisma; Irfan Amir; Zulfadli Zulfadli (Institut Agama Islam Negeri Fattahul Muluk Papua, 2025)
The debate over shifting the mechanism for electing regional heads from direct popular election to election by the Regional People’s Representative Council (DPRD) has resurfaced in Indonesia’s constitutional discourse. This study aims to describe this shift in the mechanism for electing regional heads from the perspectives of constitutional law and regional democracy, with the principles of popular sovereignty and accountability of power serving as the primary foundations of the analysis. This study employs a normative legal research method with constitutional, conceptual, and theoretical approaches, utilizing primary and secondary legal materials such as legislation, court rulings, and relevant scholarly literature. The research findings indicate that the election of regional heads by the Regional People’s Representative Council (DPRD) is not merely a technical institutional change but carries structural implications for democratic legitimacy, patterns of local government accountability, and the quality of citizens’ political participation. This study contributes to the assertion that the various shortcomings of direct regional head elections should be addressed through reform and the strengthening of democratic institutions, not by reducing the people’s role in determining local leadership.